Transformation company management systems in Czech chemical industry - Hyršlová, Jaroslava; Branská, Lenka; Špaček, Ladislav (Univerzita Pardubice, 2007)
In relation to companies entering the global market environment, the need to carry out the company management with regard to the quality, environment and health and safety has been increasing. To provide for this requirement, companies implement the management systems (i.e. quality management systems, environmental management systems and health and safety management systems). The authors of the paper carried out a research in the second half of 2005 to analyze the current state of the management systems implementation at enterprises of the selected industry sector (including the options of their integration). They focused on chemical enterprises in the Czech Republic. The research realized in cooperation with the Association of Chemical Industry of the Czech Republic aimed at the types of management systems, at the reasons for their implementation and at their real effects and drawbacks. Furthermore, the attitudes of the chemical company management to building or transfer to the integrated management systems were the centre of attentation. The paper summarizes the objectives, methodology and main conclusions of the primary research.
Keywords: podnikový management; transformace řízení podniku; chemický průmysl; Česká Republika